Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Coffe Shop Nurona Space di Kota Bandung - Rizki Ayu Utari; Hendrawan Hendrawan; Raden Haerudjaman (Ma'soem University, 2023)
This study aims to determine the effect of service quality on customer satisfaction at Caffe shop Nurona Space in Bandung. In this study, the method used is Independent Variable and Dependent Variable, the research used is primary and secondary with data collection methods using questionnaires. The number of research samples used were 50 customers, the analysis obtained by accidental simply method used is the validates and reliability test, multiple linear, t test, spss and f test. From the research results show Quality of Service a positive and significant effect on customer satisfaction at the Nurona Space coffee shop.